Clinico-Epidemiological Profile of Viral Sexually Transmitted Infections in Seropositive Patients Attending a Tertiary Care Hospital in North India. (July 2017) - Chugh, Shikha; Garg, Vijay Kumar; Sarkar, Rashmi; Sardana, Kabir
Sexually transmitted diseases are a major public health problem both in developing and in developed countries, and especially with the co-synergy with HIV infection, there is an increasing need to have a proper understanding of the clinicodemographic patterns of sexually transmitted infections (STIs) for planning and implementing control strategies. Worldwide, there is an increased preponderance of viral STIs. Increasing incidence and altered clinical presentation of viral STIs in patients with HIV pose a diagnostic challenge; thereby, we studied the demographic profile of HIV-seropositive patients and compared clinical manifestations of viral STIs in HIV-seropositive patients to those in seronegative individuals. Twenty-seven HIV-seropositive patients with viral STI (herpes/molluscum/warts) and same number of age-, sex-, and STI-matched seronegative patients were studied for variability in clinical profile. There were significant differences in the demographic factors (education, income, and migration) and sexual practices (number of contacts and source of infection) in the 2 groups. Lesional symptoms, increased extent of lesions, and resistance to treatment were significantly more common in HIV-seropositive patients.